Analysis Of Potential Zone Catching Of Yellow Fin Tuna (Thunnus Albacares) Based on Aqua Modis Images in Cilacap Waters - Beta Indi Sulistyowati; Kadi Istrianto; Pandu Damar Sukma (Fakultas Perikanan dan Ilmu Kelautan Universitas 17 Agustus 1945 Cirebon, 2022)
One area that has the potential for Yellowfin Tuna (Thunnus Albacares) is in the southern area of ​​Java, especially the Cilacap sea waters. To increase efficiency in the search for fishing areas, technology is needed that can determine potential fishing areas. One technique for determining fishing areas is by utilizing remote sensing technology using oceanographic parameter image data via the Aqua MODIS satellite. The oceanographic parameters used were chlorophyll-a and sea surface temperature (SST). The content of chlorophyll-a in the waters for yellowfin tuna (Thunnus Albacares) ranges from 0.15 mg/m3 – 0.17 mg/m3 . The sea surface temperature (SST) for Yellowfin Tuna (Thunnus Albacares) ranges from 26OC - 29OC. From the results of the analysis of mapping, the waters in the sea area of ​​​​Cilacap is a suitable habitats marked by the number of coordinates of the Potential Fishing Zone (ZPPI).